Fostering Religious Moderation in Generation Z: The Impact of Cultural Environment and Social Media - Relit Nur Edi; Hervin Yoki Pradikta; Khavid Normasyhuri (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The objective of this research is to explore the relationship between the cultural environment, social media, and religious moderation among Generation Z in Lampung Province. This study utilizes a quantitative research methodology supported by SmartPLS 3.0 software. Primary data was collected using a purposive sampling method, focusing on Generation Z in Lampung Province, with a total of 500 respondents. Data collection was conducted via Google Forms, and responses were evaluated using a Likert scale. The findings reveal a path coefficient of 0.409, coupled with a notably high t-statistic value of 6.345 and a p-value of 0.000. These results provide empirical evidence that the cultural environment exerts a positive influence on religious moderation within Generation Z in Lampung Province. Likewise, a path coefficient of 0.350 and a t-statistic value of 5.354, which surpasses the critical threshold of 1.96, along with a p-value of 0.000, indicate that social media positively impacts religious moderation in this cohort as well. In summary, the research underscores the significant roles that both the cultural environment and social media play in shaping religious moderation among Generation Z in Lampung Province. This study adds to the existing literature by examining the interplay between cultural and technological influences on the religious behaviors of young people. By understanding how local and global cultural values disseminate through social media and shape attitudes towards religious moderation, the findings offer valuable insights into the sociology of religion. Practically, these insights are essential for policymakers, educators, and religious institutions in crafting programs that promote diverse religious moderation. Such initiatives are crucial for preventing polarization, fostering tolerance, and enhancing social cohesion in an ever-changing landscape.